Leadership six studies in World strategy - Kissinger, Henry (London Penguin Audio, 2022)
In Leadership, Kissinger analyses the lives of six extraordinary leaders through the distinctive strategies of statecraft, which he believes they embodied. After the Second World War, Konrad Adenauer brought defeated and morally bankrupt Germany back into the community of nations by what Kissinger calls ?the strategy of humility.? Charles de Gaulle set France beside the victorious Allies and renewed its historic grandeur by ?the strategy of will.? During the Cold War, Richard Nixon gave geostrategic advantage to the United States by ?the strategy of equilibrium.? After twenty-five years of conflict, Anwar Sadat brought a vision of peace to the Middle East by a ?strategy of transcendence.? Against the odds, Lee Kuan Yew created a powerhouse city-state, Singapore, by ?the strategy of excellence.? And, though Britain was known as ?the sick man of Europe? when Margaret Thatcher came to power, she renewed her country?s morale and international position by ?the strategy of conviction.?
Keywords: Leadership